المبادئ الأساسية لبناء النظرية الاجتماعية في المجتمعات العربية والإسلامية - غربي, عبد الناصر; حمي, سليم (University of Eloued جامعة الوادي, 2016)
إن النظرية الإسلامية هي البديل العربي المقترح لتجاوز السوسيولوجيا الغربية، والتي تم تأصيلها على أسس إسلامية محضة، مع الاعتماد الفكر الإنساني في بناء السوسيولوجيا البديلة، وذلك من خلال استقراء التراث الإسلامي للوصول إلى بنية نظرية تختلف عن نظيرتها الغربية. إذن، ما النظرية الإسلامية في مجال السوسيولوجيا؟ ومن هم أبرز روادها وممثليها؟ وما أهم مرتكزاتها النظرية والمنهجية والتطبيقية؟ وما هي أهم استراتيجيها؟ وما هي أهم مقوماتها؟ ثم ما هي أهم الانتقادات الموجهة إليها؟ The Islamic theory is the Arabic substitute proposed to bypass the western sociology. It emerged years ago, aiming at consolidating a real radical social theory, relying on the Quran and Sunnah and the Islamic and the human thought, through the extrapolation of Islamic heritage to reach a theoretical structure which differ from Western counterparts. So, what is the Islamic theory in the field of sociology? Who are its leaders and representatives? What are the most important theoretical, methodological and applied orthodoxies? What are its most important theoretical and applied strategy? What are its key components? And what are the most important criticism to this theory? That is what we learn about through this intervention
The basic principles for the construction of social theory in the Arab and Islamic societies
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: النظرية الاجتماعية الإسلامية، التصور النظري والمنهجية والتطبيقية، الاستراتيجيات النظرية والتطبيقية; The Islamic social theory, the theoretical concept and the applied methodology, Theoretical and applied strategies